Rohingya Ethnic Muslim Minority and the 1982 Citizenship Law in Burma - Haque, Md. Mahbubul (Journal of Muslim minority affairs, 2017)
The Rohingyas have experienced difficulties in obtaining citizenship since the enactment of the 1982 Citizenship Law in Burma. From the beginning of Burmese independence, their separate identity was recognized by the then democratic government of Premier U Nu (1948-1962). Their situation worsened after the military takeover in 1962 leaving then subject to humiliating restrictions and harsh treatment by the State. However, the Burmese 1982 Citizenship Law institutionalized the Rohingyas statelessness.This paper argues that despite all evidence as indigenous people of Arakan, the ethnic Muslim minority Rohingya are arbitrarily deprived of their citizenship. The Burmese are adamant that the Rohingyas are Bengalis regardless of their residency history, and therefore belong in Bangladesh. Their Islamic religion and Indo-Aryan appearance do not conform with the "Burmese citizenship standard". In this context, Burma/Myanmar citizenship law fails to meet the international standard. Rohingya ancestry related documents prove that the government enacted the new law simply to deny the Rohingya identity.